Firm growth and R&D expenditure - Alexander Coad; Rekha Rao (Max Planck Institute of Economics, 2007)
We apply a panel vector autoregression model to a firm-level longitudinal database to observe the co-evolution of sales growth, employment growth, profits growth and growth of R&D expenditure. Contrary to expectations, profit growth seems to have little detectable effect on R&D investment. Instead, firms appear to increase their total R&D expenditure following growth in sales and growth of employment. In a sense, firms behave 'as if' they aim for a roughly constant ratio of R&D to employment (or sales). We observe heterogeneous effects for growing or shrinking firms however, suggesting that firms are less willing to reduce their R&D levels following a negative growth shock than they are willing to increase R&D after a positive shock.
Keywords: L20; L10; O32; 330; Firm Growth; Panel VAR; R&D expenditure; Industrial Dynamics; Unternehmenswachstum; Industrielle Forschung; Forschungskosten; USA